Reconstructing Islamic Theology Beyond Classical Exegesis: Muhammad Shahrur's Hermeneutical Reconfiguration of Islam and Iman - Moh. Nor Ichwan (Jurnal Theologia, 2025)
This article examines Muhammad Shahrur's contemporary Qur'anic hermeneutics as an attempt to reconstruct Islamic theology beyond the framework of classical interpretation. The analysis unit of this research focuses on the reinterpretation of the concepts of Islam and faith, and on the foundation of Islamic normativity, in Shahrur's main work, especially al-Islam wa al-Iman: Mandhumah al-Qiyam. This study aims to analyze how Shahrur's hermeneutic method challenges traditional theological assumptions and offers an alternative understanding of religious obligations and their relationship with human nature. This research uses a qualitative approach grounded in a literature review, with content and comparative analyses of Qur'anic texts and classical interpretations. The study's findings show that the conceptual separation between Islam and faith, and the reconstruction of the pillars of Islam proposed by Shahrur, constitute significant hermeneutical innovations that redefine Islamic normativity in a more inclusive and contextual manner. This article contributes to the development of contemporary Islamic thought by offering a critical framework for reinterpreting theological concepts in the face of the epistemological and social challenges of the modern world.